2014
DOI: 10.1007/s00498-014-0124-z
|View full text |Cite
|
Sign up to set email alerts
|

Recovering the observable part of the initial data of an infinite-dimensional linear system with skew-adjoint generator

Abstract: We consider the problem of recovering the initial data (or initial state) of infinite-dimensional linear systems with unitary semigroups. It is well-known that this inverse problem is well posed if the system is exactly observable, but this assumption may be very restrictive in some applications. In this paper we are interested in systems which are not exactly observable, and in particular, where we cannot expect a full reconstruction. We propose to use the algorithm studied by Ramdani et al. in (Automatica 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 45 publications
1
31
0
Order By: Relevance
“…Appendix) u + is in the energy space (19) and u − is in the corresponding energy space on [−T, 0]. As K ⊂ M int , we see that u belongs to the space (9). Lemma 4 implies that U 0 = 0.…”
Section: Energy Identity and Unique Continuationmentioning
confidence: 92%
See 1 more Smart Citation
“…Appendix) u + is in the energy space (19) and u − is in the corresponding energy space on [−T, 0]. As K ⊂ M int , we see that u belongs to the space (9). Lemma 4 implies that U 0 = 0.…”
Section: Energy Identity and Unique Continuationmentioning
confidence: 92%
“…Let us now consider the general case where u is in (9). Let ψ ∈ C ∞ 0 (− /2, /2), where > 0 is small.…”
Section: Energy Identity and Unique Continuationmentioning
confidence: 99%
“…In the latter article the method is called time reversal focusing and they treat the concrete problem of retrieving the initial state of the Kirchhoff plate equation from partial field measurements. Further development of the BFN method includes [10] by Haine showing a partial convergence result when the exact observability assumption is not satisfied, and [9] by Fridman extending the result to a class of semilinear systems. Application to unbounded computational domain is considered by Fliss et al in [8], and a variant for systems containing a diffusive term is suggested by Auroux et al in [4] where the idea is to change the sign of the diffusive term in the backward phase.…”
Section: Problem Setup and The Back And Forth Nudging Methodsmentioning
confidence: 99%
“…We shall show this only in the skew-adjoint case, but a similar variant for ESAD systems is possible. In addition, we again make the exact observability assumption, but this theorem can be straightforwardly generalized to the non-observable case as is done in [10]. In that case the convergence is not exponential and of course the minimizer is not necessarily unique.…”
Section: 2mentioning
confidence: 99%
“…• If z ∈ ImT ⊕ (ImT ) ⊥ , then the set argmin ψ∈X T ψ − z 2 is closed, convex and non-empty (in particular (8) admits at least one solution).…”
Section: 2mentioning
confidence: 99%